Allometric growth of Panulirus gracilis (DECAPODA: PALINURA) associated to the gonad maturity stages - Borrego-Durán, Jennifer Zoe; Pérez-González, Raúl; Rodríguez-Domínguez, Guillermo; Ignacio-Borrego, Martin; Félix-Ortiz, José Adán; Arzola-González, Juan Francisco; Gutiérrez-Rubio, Yecenia; Payán-Alejo, Jorge (Ecosistemas y Recursos Agropecuarios, 2024)
The relative growth on spiny lobster Panulirus gracilis was analyzed a multimodel selection approach and Akaike information theory. In the carried out samples at the landing commercial of spiny lobster, at the south of Sinaloa, Mexico during season 2014 and 2015, and 2017 and 2018. In 298 female P. gracilisindividuals were measures caparace length (CL) mm, total weight (W) g, and gonad maturity stages. The structure sizes between 54.6 to 103.1 mm CL. The organism minor size mature was 57.5 mm CL but maturity percent stages rise on larger sizes. The best model was broken stick (Wi = 65.09%) but also two segments has statistic support (Wi=34.87%). A differential relative growth in both models, coincident with a rise in the percent gonad maturity toward big sizes in P. gracilis.
Keywords: Lobster; allometric; maturity; multimodel selection